Effect of perioperative blood loss on cognitive function disorders after colon cancer surgery - Dalibor P. Bošković; Sanja Marić; Marko Kovačević; Bojan Golijanin (Биомедицинска истраживања, 2022)
Introduction: Postoperative cognitive dysfunction (POCD) is very common in patients who are treated in intensive care units or in the surgery department after surgery. This increasingly present complication complicates and calls into question the recovery of the operated patient. We assumed that POCD was associated with blood loss in patients undergoing colorectal cancer surgery. Methods: Our study included 60 patients older than 50 years who underwent elective open surgery for colon cancer. The same protocol was performed for each patient: preoperative preparation and anesthesia. All patients completed three psychometric tests (mini mental test - MMT, information test and Hooper test) the day before surgery, one day after surgery and the seventh day after surgery. Results: Cognitive status examined on the basis of the MMT score showed a statistically significant difference in the number of received blood transfusions after surgery on the first day (p = 0.016) and the total number of received blood transfusions (p = 0.026). Cognitive status examined by the information test showed a statistically significant difference (p = 0.025) in the number of received blood transfusions after surgery on the first day. In patients whose cognitive status was examined by the Hooper test, a high statistically significant difference was observed in the number of received blood transfusions after surgery on the first day (p = 0.001). Cognitive status measured on the basis of MMT score showed that there was a statistically significant difference in the average values of the amount of blood given by transfusion after surgery (p = 0.019). Conclusion: There was a statistically significant cognitive dysfunction in patients who had greater blood loss during surgery and the first day after surgery and who received more blood transfusions (more than 600 ml) during and after surgery. The introduction of psychometric tests in the assessment of cognitive functions as well as the choice of surgery may be important factors in the prevention of POCD.
Keywords: cognitive dysfunction; blood loss; psychometric tests; colorectal cancer